Pengaruh Kelancaran Transaksi, Keamanan Tabungan, Kemudahan Penggunaan terhadap Loyalitas Pengguna Gen Z Aplikasi Bank Jago - Auliya, Audy; Dara, Siti Ruhana (KALBISOCIO Jurnal Bisnis dan Komunikasi, 2026)
The purpose of this research is to determine the partial and simultaneous influence of transaction smoothness, savings security, and user convenience on user loyalty of the Bank Jago application. The research method used is a quantitative approach. The sampling technique used was non-probability sampling and the sampling used was purposive sampling with a sample of 180 people. The target respondents were Gen Z as users of the Bank Jago application in Jakarta. The measurement scale in this study used a Likert scale. The measuring instrument used is a questionnaire. Data analysis using multiple linear regression models. The results of this study indicate that transaction smoothness has no influence on user loyalty, savings security and ease of use partially have an influence on user loyalty, and transaction smoothness, savings security, and ease of use simultaneously have an influence on user loyalty.